Exploring the relationship of prospective primary teachers with mathematics and statistics: memories, emotions and turning points - Capomagi, Gemma; Aguilar-González, Álvaro; Rodriguez-Muñiz, Luis J. (LUMAT-B: International Journal on Math, Science and Technology Education, 2024)
This study explores the relationship between prospective primary teachers and mathematics. Data was collected from prospective primary teachers enrolled in an undergraduate program. The excerpts have been analysed through Grounded Theory. From the analysis conducted, participants’ self-concept regarding the subject, the influence of academic performance and the teacher, and the utility of mathematics in everyday life have emerged as relevant codes. The study identifies turning moments in the participants’ educational journeys, generated by the extrinsic factors, which influence the intrinsic ones. Finally, particular attention is given to probability and statistics.